Consciousness and society - "Hughes, H. Stuart" (New brunswick, 2004)
Hughes' ideas, and the way they are expressed in Consciousness and Society, have become paradigms of twentieth-century scholarship. In dealing with the changing social thought after 1890 in Europe, Hughes covers a wide array of thinkers and issues in a scholarly, yet graceful manner. His is a study of the "cluster of genius" of Europe at that time: Croce, Durkheim, Freud, Weber, and Nietzsche, as well as other great European minds. The book explores questions that are still relevant in today's society: Is the separation of facts and values tenable, or even desirable? Can rationality accommodate the ideas of a Bergson or a Freud? Is there, or should there be, a relationship between science and religion? And does history have any ultimate meaning for later generations?
Keywords: Social science-Philosophy